Inovasi Teknologi Alat Pembuat Petis Ikan Otomatis Pada Desa Lebak Barat Pamekasan Madura - Ikawanty, Beauty; Fitri, Fitri; Kurnia Safitri, Hari; Irawan, Bambang; Hadiwinata, Khrisna; Christiawan Firmansyah, Rizky; Zul Chandyas, Sirat (J-Dinamika : Jurnal Pengabdian Masyarakat, 2024)
Partners in the PPM Partnership program is fish steamer and paste maker in West Lebak Village, Pamekasan Madura. In the process of steaming partner fish, firewood is still used as fuel. This causes air pollution in the surrounding environment; workers complain of heat and sore eyes. With these partner conditions, there is potential to develop an automatic fish steamer. Apart from that, the workers complained that the process of stirring the fish paste took a long time and had to be stirred constantly so that the fish paste didn't burn. The methods used in this program are appropriate technological innovation, training and coaching as well as monitoring and evaluating activities. Technological innovation was carried out through the creation of fish steamers and automatic fish paste makers using LPG gas. Training and guidance are carried out through activities on how to use and maintain fish steamers and automatic fish paste makers, how to prepare documents and register distribution permits. Partners prepare fish ingredients for the smoking process, provide a place for training and prepare training participants and demonstrations that will be carried out by the service team. The technological innovation of the automatic fish steamer produces a temperature of 90o with a time of 30 minutes to cook around 10 kg of fish. Meanwhile, the automatic fish paste maker produces a stable temperature of 70o with a paste cooking process for 3 hours